Outcome of Adjuvant Concurrent Chemo-Radiation in Operated Locally Advanced Rectal Cancer (Journal of Enam Medical College, 2015)
Background: Rectal cancer is one of the most common cancers in Kashmir, India. The clinical course of patients treated with surgery alone has been characterized by a high death rate and also by the pain and disability associated with pelvic recurrence of the tumor. Adjuvant radiation combined with chemotherapy has been studied for prevention of such recurrences. We treat more than 200 rectal cancer patients annually at our center. Most of the patients registered at our center are those who have been already subjected to surgery at the peripheral hospitals. We studied role of 5-fluorouracil (5-FU) and calcium leucovorin concurrently with radiotherapy in Dukes stage B2 and C and toxicities thereof in the adjuvant setting.Objective: To assess the outcome of concurrent chemoradiation in operated locally advanced treated cancer patients.Materials and Methods: In operated Dukes B2 and C rectal cancer patients, we conducted a prospective non-randomized study comprising of 40 patients between 2012 and 2014. Patients were treated with two hours protracted infusion of calcium leucovorin 500 mg/m2 on day 1 followed by 5-fluorouracil 500 mg/m2 on days 1 to 5 and repeated four weekly for total of six cycles. Radiotherapy of 45 Gray in 20 fractions was delivered concurrently with chemotherapy for first two cycles.Results: Combination of chemotherapy and radiotherapy in a concurrent setting appears to be more efficient in reducing local recurrence rates and improving survival than either modality alone. Toxicities with this schedule were mostly gastrointestinal mucositis, but no treatment interruption was needed.Conclusion: A combination of 5-fluorouracil and radiotherapy can be administered in operated locally advanced rectal cancer patients.J Enam Med Col 2015; 5(3): 139-144